The study of the body of knowledge of herniated disc treatment of a folk healer - วิริยะบุบผา จุฬาำ; ภุมริน ศราวุฒิ; กิจจาสวัสดิ์ ณัฐพร; เนียมสุวรรณ อรทัย (Journal of Medicine and Health Sciences, 2018)
This qualitative research aimed to study folk knowledge in herniated disc treatment from Mr. Chum Khummanee, a folk healer in Songkhla provinve. It was carried out by in-depth interview, participant observation and structured interview. The treatment process collected in the study were compared to the royal massage and anatomical position. According to the folk healer’s concept, it was found that herniated disc was initially caused by muscle or backbone injury. If the disorder was not treated correctly, the nerves would be pressured by fascia. Then, the wind element will be obstructed that it affected to the blood circulation in the body. The final symptoms were presented with back pain, radicular pain to the area of the bottom (Boh Luead), legs, and feet including with numbness. There were two treatment methods i.e. 1) massage treatment with stretching, and 2) herbal medicine, which were his own knowledge. However, the treatment methods in each case probably varied depending on their severity of symptoms. From the data analysis, folk-massage treatment conforms to the royal massage pattern, both in basic and signal points of massage. In addition, the folk massage agrees with those in anatomical position including muscles, tendons, blood vessels, and nerves.